Особливості вторинної профілактики ішемічної хвороби серця у робітників транспорту - Телятников, О.В. (Актуальні проблеми транспортної медицини, 2010)
Обследовано 52 больных со стенокардией напряжения ИИ ИИИ ФК на фоне артериальной гипертензии, атерогеноq дислипопротеинемии и сердечной недостаточности, которые прини мали аторвастатин в суточных дозах 10 и 20 мг, что привело к повышению уровня NO синтазы, уровня нитратов и снижения нитритов на фоне базисной терапии, в сравнении с базисной терапией без аторвастатина. Examinated 52 patients with Stenocardia of tention II III Functional Classes (FC) with arterial hipertention (AH),heart insufficiency and atherogenic dislipoproteinemia, who took atorvastatin (daily dose 20 mg), what led to increase of NO sуntase activity, content of nitrites had decreased, content of nitrates had increased. In another group of patients, that didn’t receive statins, wasn’t observed increase of activity NO sуntase in blood plasma.